PERAN FOOD AND AGRICULTURE ORGANIZATION (FAO) DALAM MENINGKATKAN KETAHANAN PANGAN DI PROVINSI NUSA TENGGARA TIMUR MELALUI PROGRAM PERTANIAN KONSERVASI - Romano Besin Berek (Universitas Komputer Indonesia, 2018)
One of the background case that arise in this research are the drasticaly climate change with frequent drought in NTT province and low food security level so the presence of FAO with Conservation Farming program that is expected to helingp NTT achieve their Food Security. This research aims to describe the role of Food and Agriculture Organization (FAO) through Conservation Agriculture Program in improving Food Security in East Nusa Tenggara Province (NTT), the researcher also intends to know how the implementation process of Conservation Agriculture in NTT Province and to know what are the constraints which FAO faces in the implementation of Conservation Agriculture (CA), and how the progress and plans of the FAO continue after the end of this program.